Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\frac{x+5}{x+1}=\frac{x+4+1}{x+1}=\frac{x+1}{x+1}+\frac{4}{x+1}\)
\(\Rightarrow x+1\in\text{Ư}\left(4\right)=\left\{1;2;4;-1;-2;-4\right\}\)
\(\Rightarrow x\in\left\{0;1;3;-2;-3;-5\right\}\)
x+5\(⋮\)x+1
x+1+4\(⋮\)x+1
Vì x+1\(⋮\)x+1
Buộc 4\(⋮\)x+1=>x+1ϵƯ(4)={1;2;4}
Với x+1=1=>x=0
x+1=2=>x=1
x+1=4=>x=3
Vậy xϵ{0;1;3}
Giải:
Ta có:
\(x+8⋮x+1\)
\(\Rightarrow\left(x+1\right)+7⋮x+1\)
\(\Rightarrow7⋮x+1\)
\(\Rightarrow x+1\in\left\{1;-1;7;-7\right\}\)
+) \(x+1=1\Rightarrow x=0\)
+) \(x+1=-1\Rightarrow x=-2\)
+) \(x+1=7\Rightarrow x=6\)
+) \(x+1=-7\Rightarrow x=-8\)
Vậy \(x\in\left\{0;-2;6;-8\right\}\)
\(\frac{x+8}{x+1}=\frac{x+7+1}{x+1}=\frac{x+1}{x+1}+\frac{7}{x+1}\)
\(\Rightarrow x+1\in\text{Ư}\left(7\right)=\left\{1;7;-1;-7\right\}\)
\(\Rightarrow x\in\left\{0;6;-2;-8\right\}\)
\(\frac{x+4}{x}=\frac{x}{x}+\frac{4}{x}\)
\(\Rightarrow x\in\text{Ư}\left(4\right)=\left\{1;2;4;-1;-2;-4\right\}\)
Ta có :
\(x+4⋮x\)
=> \(x+4-x⋮x\)
=> \(4⋮x\)
=> \(x\inƯ_4\)
=> x\(\in\left\{1;2;4;-1;-2;-4\right\}\)
Ta có :
\(9⋮2x+1\)
=> \(2x+1\inƯ_9\)
=> \(2x+1\in\left\{1;3;9\right\}\)
=> \(2x\in\left\{0;2;8\right\}\)
=> \(x\in\left\{0;1;4\right\}\)
Vậy \(x\in\left\{0;1;4\right\}\)
a) \(3^{x+1}=729\)\(\Leftrightarrow3.3^x=729\Rightarrow3^x=243\Rightarrow3^x=3^5\Rightarrow x=5\)
b) \(2^x+2^{x+1}+2^{x+3}=704\Rightarrow2^x+2^x.2+2^x.2^3=704\Rightarrow2^x\left(1+2+8\right)=704\)
\(\Rightarrow2^x.11=704\Rightarrow2^x=64\Rightarrow2^x=2^5\Rightarrow x=5\)
1)
\(\frac{3}{4}.x+\frac{x}{5}=\frac{1}{6}\)
\(x.\left(\frac{3}{4}+\frac{1}{5}\right)=\frac{1}{6}\)
\(x.\frac{19}{20}=\frac{1}{6}\)
\(x=\frac{1}{6}:\frac{19}{20}\)
\(x=\frac{10}{57}\)
2)
\(x+3\frac{1}{2}+x=24\frac{1}{4}\)
\(2x+3\frac{1}{2}=24\frac{1}{4}\)
\(2x=24\frac{1}{4}-3\frac{1}{2}\)
\(2x=\frac{83}{4}\)
\(x=\frac{83}{4}:2\)
\(x=\frac{83}{8}\)
\(x+1⋮x-1\)
\(x-1+2⋮x-1\)
\(2⋮x-1\)hay \(x-1\inƯ\left(2\right)=\left\{\pm1;\pm2\right\}\)
x - 1 | 1 | -1 | 2 | -2 |
x | 2 | 0 | 3 | -1 |
\(x-2⋮x+1\)
\(x+1-3⋮x+1\)
\(-3⋮x+1\)thự hiện tương tự nhé !
\(\frac{x+1+3}{x+1}=\frac{x+1}{x+1}+\frac{3}{x+1}\)
\(\Rightarrow x+1\in\text{Ư}\left(3\right)=\left\{1;-1;3;-3\right\}\)
\(\Rightarrow x\in\left\{0;-2;2;-4\right\}\)
Ta có :
\(x+1+3⋮x+1\)
=> \(x+1+3-\left(x+1\right)⋮x+1\)
=> \(3⋮x+1\)
=> \(x+1\inƯ_3\)
=> \(x+1\in\left\{1;3;-1;-3\right\}\)
=> \(x\in\left\{0;2;-2;-4\right\}\)